SME Finance in Chile : Enhancing Efficiency of Support Programs - World Bank (World Bank, Washington, DC, 2020)
This review of small and medium-sized enterprise (SME) finance support programs aims to enhance the efficiency of SME finance support in Chile. Chile’s good economic policies have successfully promoted growth, but inequality has remained high. Supporting access to finance for SMEs is an important part of developing more equal opportunities in Chile. The purpose of the analysis is to identify options for strengthening corporacion de fomento de la produccion (CORFO’s) role in addressing the SME finance gaps arising from market failures. The study focuses on determining if the various partial credit guarantee (PCG) programs are efficient and optimal in their design and how CORFO’s role can be expanded to support SMEs. To achieve a new more complex role, the study also considered that CORFO as an institution needed to be more self-contained and autonomous in terms of financial risks and reserving, and have a corporate structure more akin to a public owned corporation rather than a budget supported state agency. In order for the programs to have the desired effects, they must adequately address the gap, be effectively implemented, and be cost efficient. The paper is organized as follows: section one gives summary, section two gives introduction. Section three analyzes the gap in finance for SMEs in Chile to establish the relevance of the programs. Section four provides an overview of programs in support of SME finance, the implementation effectiveness, and the associated costs. Sections five to seven presents recommendations.